Effectiveness of breastfeeding for pain relief in infants during vaccination at Bharatpur - Gurung, Anjana; Bajracharya, Subina (International Journal Of Community Medicine And Public Health, 2021)
Background: Vaccination is an integral part of childhood development since it protects children from a variety of diseases. It is, however, the most common cause of pain in children. Breastfeeding is effective tool for reducing pain in infants during vaccinations. The objective of the study was to determine the effectiveness of breastfeeding for pain relief in infants during vaccination. Methods: A true experimental pretest and posttest design was conducted at Maternal and Child Health Clinic at Bharatpur, Nepal among 140 infants receiving pentavalent vaccines (Diphtheria, Pertussis, Tetanus, Hepatitis B and Hemophilus influenzae B). A structured interview schedule was used to collect socio-demographic information of mothers and infants. Bio physiologic method was used to determine biological and physical status of the infants. Modified behavioral pain scale was used to measure the level of pain in infants in both the control and experimental groups. Results: The study revealed that the total modified behavioral pain scale (mean ±SD after vaccination was 8.74±0.53 in control and 8.23±1.07 in experimental respectively. The study showed that breastfeeding had significantly lowered pain level (p<0.001) and lessened duration of cry (p=0.002) in infants in experimental group than in control group after vaccination. However, related to injectable vaccination, the study showed that breastfeeding did not significantly stabilized heart rate in infants in both the groups (p=0.122). Conclusions: The study concluded that the infants who were breastfed experienced less pain than those who were not breastfed during vaccination.